Social Enterprise: Creating an Equitable Strategy in Entrepreneurship towards Achieving Competitive Advantage - Kampetch, Pornpimon; Lukanathinakorn, Nongluk; Sriharan, Parichart (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The operation of business sector that aims to enable the organization to grow and to survive the changing scenario invokes the searching of executives and leaders to achieve organization readiness. In the past the entrepreneurial activity had emphasized on intensive competition to become the monopoly and to dominate the market while limiting competitors in the market; this is called “Red Ocean Strategy” which may cause a subsequent disadvantage. At the present day choosing a practical strategy depends on a situation and conscience of the entrepreneurs who seek means to the new entrepreneurship that focuses on the form of business venture that creates good relation between all stakeholders. This brings about equitability concurrently with the solution to societal and environmental causes. Further, it generates revenue for the mobilization of business ventures to grow similarly to the Green Ocean Strategy and the White Ocean Strategy. The new business paradigm is the value creation that consolidates resources all together to create change or to mainly respond to social needs which is called “Social Entrepreneurship” through the provision of merchandises (goods) and services. Therefore, it is a posing challenge to individuals or groups who will become social entrepreneurs for the establishment of social enterprise by creating social innovations such as searching for new ideologies; and setting up an organization to bring about positive social change while creating value for all stakeholders including consumers, producers, and communities that devise new creations to society.